SURGICAL TACTICS REGARDING CEREBRAL METASTASES WITH HEMORRHAGES - E. V. Prozorenko; V. B. Karakhan; A. Kh. Bekyashev; V. A. Alyoshin; D. M. Belov; D. R. Naskhletashvili; N. V. Sevyan; A. A. Mitrofanov (Опухоли головы и шеи, 2015)
Cerebral metastases occur with 10 to 30 % of all oncological patients. Hemorrhages into cerebral metastases are one of the most dangerous complications of the metastatic process. With that, cerebral metastases of such widespread solid malignant tumors as melanoma, kidney cancer, germ cell tumors, less frequently, lung cancer and breast cancer are prone to hemorrhages. The purpose of the work is to improve the results of surgical treatment of patients with brain metastases complicated with hemorrhages.Materials  and  methods. Surgical  treatment  of  69  patients  with  brain  metastases complicated  with  hemorrhages was  performed in N.N. Blokhin Russian Cancer Research Center. Hemorrhage on the macroscopic level was confirmed intraoperatively and in accordance with the results of the morphological study of surgical drugs. Total microsurgical resection of one or several cerebral metastases with hemor rhages was performed regarding all patients studied. The time interval of observation of patients after the surgical treatment comprises 1 to 72 months. There were 27 women and 42 men. The age range was from 18 to 74 y.o. Besides, the state of veins of lower extremities and the state of the coagulation blood system in accordance with the data of coagulograms was studies. The analysis of the macrostructure and the microstructure of metastases with hemorrhages as well as the morphological study of the brain tissue adjacent to hematomas was performed with a morphological study and histological techniques. The patients were distributed in accordance with the RPA (recursive partitioning analysis) classes: I class (n = 7), II class (n = 39), III class (n = 23); in accordance with the hemorrhage type: intratumoral type (26 metastases), perifocal type (20), mixed type (32); in accordance with the histological principle: melanoma (n = 25), lung cancer (n = 13), kidney cancer (n = 17), breast cancer (n = 4), colorectal cancer (n = 1), soft tissue sarcoma (n = 4), non-seminomatous germ cell tumor (n = 5).Results. Early post-surgical lethality comprised 6 % (n = 4). Development of local relapses comprised 16 % (n = 11). Extracerebral development of the disease has become the reason of death of 59 % of patients, development of the disease in the brain has become the reason of death of 41 % of patients. The shortest survival median was found with patients suffering from melanoma and comprised 6 months, with the III class of RPA, it comprised 6 months, with the perifocal hemorrhage type, it comprised 6 months, the longest survival median was found with patients suffering from sarcoma and comprised 15.5 months, with the I class of RPA, it comprised 14 months, and with the intratumoral hemorrhage type, it comprised 14.5 months.Conclusions. Development of local relapses depended on the surgical intervention technique and did not depend on the availability of tumor elements in the hematoma. Separated resection of the metastasis and perifocal hematoma does not violate oncosurgical principles and does not cause the rate of local relapses; the common survival median of patients after surgical treatment comprised 9 months. The factors that determined survival of patients with cerebral metastases with hemorrhages were the histological form of the primary tumor, type of metastasis hemorrhage and RPA class of the patient prior to the surgery.